Manajemen Nyeri pada Pasien Penurunan Kesadaran di Ruang Perawatan Intensif : scooping review - Silviani, Sinta; Trisyani, Yanny; Emaliyawati, Etika (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Pain is an unpleasant sensory and emotional experience resulting from tissue damage. Unconscious patients cannot directly communicate their pain to nurse, but this doesn’t meant they cannot feel pain. Pain in unconscious patients can arise from routine procedures such as prolonged immobilization to invasive procedures like surgery. Nursing interventions to manage pain are necessary to enhance patient comfort. This study aims to examine pain management in unconscious patients in the Intensive Care Unit. This type of research is a scoping review, searching for articles in the PubMed, SCOPUS, and EBSCO databases. The search process used keywords (unconscious patient OR coma OR sopor OR somnolent) AND (pain management OR pain relief OR pain control) AND (intensive care unit OR critical care OR HCU). 45 articles were found that matched the keywords, but only 5 articles were relevant to the review's objectives. Pain management for unconscious patients starts with recognizing pain symptoms, assessing pain, and followed by nursing interventions. Interventions that can be provided include TENS (Transcutaneous Electrical Nerve Stimulation), foot massage, and music therapy.  Keywords: Pain Management, Unconscious patient, ICU   ABSTRAK  Nyeri merupakan pengalaman sensorik dan emosional yang tidak menyenangkan akibat adanya kerusakan jaringan. Pasien yang tidak sadar tidak dapat mengatakan rasa nyeri yang dirasakan secara langsung pada perawat namun bukan berarti tidak dapat merasakan nyeri. Rasa nyeri pada pasien tidak sadar dapat berasal dari tindakan rutin seperti imobilisasi lama, hingga tindakan invasif yang seperti tindakan pembedahan. Intervensi perawat untuk mengatasi nyeri perlu dilakukan untuk meningkatkan kenyamanan pasien. Penelitian ini bertujuan untuk melihat manajemen nyeri pada pasien penurunan kesadaran di ruang Intensive Care. Jenis penelitian ini adalah scooping review, dengan mencari artikel pada database Pubmed, SCOPUS dan EBSCO. Proses pencarian menggunakan kata kunci (unconscious patient OR coma OR soppor OR somnolent) AND (pain management OR pain relief OR pain control) AND (intensive care unit OR critical care OR HCU).  Didapatkan 45 artikel sesuai kata kunci namun hanya didapatkab 5 artikel yang sesuai dengan tujuan review. Manajemen nyeri pasien tidak sadar dimulai dari mengenali gejala nyeri, pengkajian nyeri dan dilanjutkan dengan intervensi keperawatan. Intervensi yang dapat diberikan adalah TENS (Transcutaneous Electrical Nerve Stimulation), pijat kaki dan terapi musik.  Kata Kunci: Manajemen Nyeri, Pasien Tidak Sadar, ICU